STUDI KARAKTERISTIK DAERAH RESAPAN (GROUNDWATER RECHARGE AREA) BANDUNG SELATAN DAN SEKITARNYA, PROVINSI JAWA BARAT - Iwan Fahlevi Setiawan (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2020)
Groundwater exists in a Groundwater Basin (CAT). In a CAT the groundwater process start by enters of the waters (recharge), flows and then exits (discharge). This process is largely controlled by geological factors, the recharge area in a CAT holds an important factor in groundwater management. There are several parameters that will affect the characteristics of a CAT recharge area, which are graduation of rocks, rainfall, soil cover, slope, and unconfined ground water level (Attachment to the Minister of Energy and Mineral Resources Regulation No. 31 of 2018). The five parameters are the basis for this research to study the characteristics of the recharge area through the assessment and weighting method and overlapping to obtain certain values. Bandung Regency and its surroundings from hydrological conditions have high rainfall and are dominated by volcanic rocks that can pass and store water (Sugianti et al., 2016). So it is interesting to examine the characteristics of the recharge area, the results of which can also be used as material for the location of Field Work Practices (PKL). The results of the analysis of the 5 (five) parameters are the conductivity value is in low groups, based on the results of precipitation data analysis, the study area is divided into 2 (two) regions, namely areas with rainfall that have a value of 1000 - 2000 mm / year and areas that have low rainfall <1000 mm / year. The results of the analysis of the soil cover parameters of the study area are divided into 2 (two) groups, with a value of 12 and a group with a weight value of 9, the results of the analysis of the slope parameters obtained by 3 (three) groups, namely regions with values slope <500 , 50 0– 1000 and 100 0– 200 0. Based on the unconfined water table (MAT) parameters in the study area, they are grouped into 2 (two) groups, namely the medium group with a weight value of 2 having a MAT depth between 5 - 10m and a low group with a value of 1 having a depth of MAT <5m. Based on the analysis of the recharge value, the South Bandung area has 3 (three) grounwater recharge areas, namely the main recharge area with a recharge value >33, additional reharge area with a recharge value 30-33, and the affixed area with a recharge value < 30. Main recharge area with value > 33 which is spread in the area around Soreang, Situ Cileunca, and part of Rancaekek is an area that has the potential for groundwater catchment.